The enhancement of M13 phage titration by optimizing the origin of replication - Mohammad Hossein Darvishali; Mahmood Fadaie; Hossein Khanahmad (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: M13KO7, a modified M13 phage variant, carries the p15A replication origin and Tn903 kanamycin resistance gene. This study aimed to optimize M13KO7's replication by substituting the p15A origin with the higher-copy pMB1 origin (500-700 copy numbers). Experimental approach: A 6431-nucleotide fragment from the M13KO7 plasmid lacking the p15A replication origin and kanamycin resistance gene was amplified using a long polymerase chain reaction (PCR). The modified M13AMB1 plasmid was created by adding adenine to the 3' ends of this fragment and ligating it to the pMB1-containing fragment using T/A cloning. Afterward, to prepare the phage, pM13AMB1 was transformed into E. coli TG1 bacteria, and then, using the PEG-NaCl precipitation, the modified phage was propagated. The modified phage titer was determined utilizing the serial dilution and the qPCR methods, compared with the M13KO7 phage. Findings/Results: The results showed that in the serial dilution method, the titers of modified phage and M13KO7 phage were 4.8 × 1014 and 7 × 1012 pfu/mL, respectively. Besides, the phage titer calculated by the qPCR method for the modified phage was equal to 1.3 × 109 pfu/mL, whereas it was 4.08 × 108 pfu/mL for the M13KO7 phage. Conclusion and implications: This study provides evidence that replication origin replacement led to a significant increase in phage titers. It highlights the importance of replication optimization for molecular biology applications.